Nutrition of neonates and infants with severe congenital heart disease - the review of the literature - Sałata, Piotr; Szczuraszek, Paulina; Szczuraszek, Hugo; Bętkowska, Paulina; Tomkiewicz, Michał; Licak, Gabriela; Tomkiewicz, Julia; Żuchnik, Magda; Olko, Paweł; Rybkowska, Agnieszka (Quality in Sport, 2023)
CHD is the most common birth defect with an incidence of 9 per 1,000 live births. The severity of the disease and the choice of treatment depend on the underlying anomaly. Despite advances in medical and surgical treatment that have led to more children with CHD reaching adulthood, disorders such as intestinal dysfunction, poor nutrition, and growth failure are still common in infants with CHD. Increased metabolic demand, decreased caloric intake, malabsorption, genetic factors, and fluid restriction can all result in an energy imbalance that negatively impacts morbidity and mortality in these patients. On the other hand, malnutrition is an important risk factor for adverse postoperative consequences. The state of nutrition affects growth and development, wound healing and the functioning of the immune system. Malnutrition affects both short-term and long-term postoperative outcomes. Recurrent infections caused by impaired immune system function and delayed healing of surgical wounds are considered short-term effects, while impaired growth, physical and cognitive development are seen as long-term effects. High postoperative mortality and morbidity, such as increased rates of hospitalization, delayed growth, prolonged recovery time, and longer hospital stays are associated with preoperative malnutrition. Appropriate nutrition protocols tailored to the requirements of patients with congenital heart disease help to improve short and long-term treatment outcomes. Nutritional and metabolic changes are age-dependent, and since this is a high-risk population, enteral and/or parenteral nutrition is difficult. Sources of increased metabolic demand in CHD include greater workload on the heart, pulmonary hypertension, and increased catecholamine secretion.